Innovative low-temperature calibration system for infrared thermometers in frozen food industry: effects of measurement distance and temperature uniformity - Manop, Dhonluck; Wangtong, Salisa; Na Ayuthaya, Worasit P.; Noulkhow, Narudom; Khaenamkaew, Panya (Frontiers in Mechanical Engineering, 2025)
IntroductionThe calibration of infrared thermometers (IRTs) in the frozen food industry is hindered by condensation on temperature reference sources in subzero environments, resulting in significant measurement errors and uncertainty.MethodsThis study investigated a novel closed-cylinder pneumatic calibration system designed to eliminate condensation using a controlled argon gas purge. The effects of gas pressure, flow rate, and measurement distance (operationalized as tube lengths of 30 cm, 50 cm, and 100 cm) on calibration accuracy were systematically evaluated.ResultsAt a chamber temperature of –15 °C, the introduction of argon at 2 kg/cm2 and 25 L/min effectively prevented ice formation on the calibration target. The system yielded expanded uncertainties ranging from 0.62 °C to 0.74 °C across all temperature set points. The shortest tube length (30 cm) provided the highest precision with minimal correction required, while 50 cm offered a reliable alternative with slightly increased uncertainty. The 100 cm tube introduced greater variability due to an increased spot size and spatial non-uniformity.DiscussionThe results demonstrate that the sealed calibration system enables accurate and reproducible IRT calibration under subzero conditions, particularly at shorter distances. This solution is especially relevant for applications in frozen food logistics, where precision temperature monitoring is essential for product safety and quality assurance.